Oppositional Omission Levels in the Linguistic Text: Text, Sentence and Word - Mustafa, Sulaf (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to concisely address the mutual deletion phenomenon within the semantic levels of the text, which can occur at the syntactic level within the sentence. It is indicated as a violation of the rules of composition in the axis of authorship, similar to how it occurs at the morphological level within the word, revealing a breach of the rules of the selection axis. Exploring this field sheds light on a phenomenon that brings together scattered elements studied in various areas, forming a comprehensive perspective on the phenomenon of oppositional omission. Methods: The study approaches oppositional omission from a semantic standpoint in the expansive space of the text, involving mutual deletion signaled by conceptual relationships. It also occurs structurally at the level of composition and morphologically through deletion between two terms, removing the form from one and the morphemic material from the other. Results: Despite the numerous discussions on oppositional omission, few researchers have precisely defined the levels at which the phenomenon occurs, clarifying the result of oppositional omission, similar to deletion in equations. Both classical and modern studies often present examples of the phenomenon without distinguishing between semantic, structural, and individual morphological levels. This lack of distinction highlights phenomena that were not previously considered under the umbrella of oppositional omission, although they are clearly related. Conclusion: Mutual deletion can multiply meanings through the reciprocal deletion between two elements at the level of a single word, a phenomenon that can be referred to as morphological omission. However, mutual deletion in many syntactic phenomena occurs continuously, as seen in the use of sources, conditional constructions, and inclusion, which can be termed as structural omission. It has been observed that only a few researchers have indicated the occurrence of omission at the level of the entire text, in the relationship between overall and detailed aspects in the structures of larger texts.